Exploring ESL Teachers’ Perspectives on Localizing English Education: Challenges and Opportunities in Integrating Local Culture into Language Teaching - Dissanayake, B.Y. (University of Jaffna, 2025)
The localization of English language education has emerged as a significant pedagogical approach aimed at making language learning more culturally relevant and engaging for students. However, English as a Second Language (ESL) teachers often encounter tensions between integrating local cultural elements and the demands of standardized English curricula. This study investigates the perspectives of experienced ESL teachers (with 5 to15 years of teaching experience) on the localization of English education, the instructional strategies they employ, and the challenges they face in implementing such practices. Framed within Vygotsky’s Sociocultural Theory and Communicative Language Teaching (CLT), the research explores how teachers mediate language learning through culturally responsive pedagogy and interactive classroom practices. Employing a qualitative narrative inquiry approach, data were collected from eight ESL teachers through semi- structured interviews. Participants were drawn from various educational institutions to ensure diversity in context and perspective. Thematic analysis was used to identify recurring patterns in teachers’ beliefs, teaching strategies, and the institutional limitations they navigate. Findings indicate that teachers perceive localization as a means to enhance student engagement and comprehension through the use of culturally relevant content, code-switching and real-world applications. However, their efforts are often constrained by curricular rigidity, the pressure of standardized testing, and institutional resistance. Teachers also expressed a need to balance linguistic authenticity with the imperative of preparing students for global communication. Despite these constraints, contextualized instruction was seen to enable student confidence and support more meaningful language acquisition. This study contributes to the broader discourse on decolonizing English education by centering the voices of practitioners engaged in pedagogical adaptation. The findings highlight the necessity of policy reform, teacher training and curriculum flexibility to support localized English instruction without compromising global standards. Future research could further explore student perspectives and the long-term impacts of localized learning on language proficiency.
Keywords: Localized English education; ESL teachers; Narrative inquiry; Sociocultural theory; Communicative language teaching